2015
DOI: 10.5755/j01.eee.21.4.12783
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ultrasound Velocity Application for Chemical Process Monitoring

Abstract: Study on the accuracy of the ultrasound velocity application for chemical process monitoring is presented. Cure degree of epoxy resins was monitored in order to establish the percentage of the final cure based on ultrasound velocity of longitudinal waves. Time of flight estimations by correlation processing were used to estimate the velocity. Sources of error in the velocity measurement and their influence in the sensitivity and accuracy of the results have been studied. In order to improve the accuracy and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The measurement of the sound velocity can also be applied for process monitoring, being remarkable for its use in the following processes, among others: alcoholic fermentation [12,13], kinetics of crystallization of palm fats [14], or epoxy curing processes [15]. Our research group demonstrated in a previous study that the real-time monitoring of the methanolysis of vegetable oils for obtaining fatty acid methyl esters (FAME) (biodiesel) is possible [16], with synthesis focused on the production of a biofuel for direct injection compression ignition engines [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the sound velocity can also be applied for process monitoring, being remarkable for its use in the following processes, among others: alcoholic fermentation [12,13], kinetics of crystallization of palm fats [14], or epoxy curing processes [15]. Our research group demonstrated in a previous study that the real-time monitoring of the methanolysis of vegetable oils for obtaining fatty acid methyl esters (FAME) (biodiesel) is possible [16], with synthesis focused on the production of a biofuel for direct injection compression ignition engines [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Adhesive bonding is widely used in vehicles manufacturing [1], aircraft industry [2], civil infrastructure such as bridges, buildings renovation or manufacturing instrumentality [3], [4]. Despite the advantages of widely used adhesives, they have drawbacks related to the need of surface preparation, necessity to avoid contaminations [5], time needed for curing the adhesive layer [6], aging and complexity of material characterization of the adhesive layer after gluing. The gluing defects can be divided into the two classes, such as adhesive and cohesive.…”
Section: Introductionmentioning
confidence: 99%